2010
DOI: 10.1155/2010/789363
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofKRASMutations of Exon 2 Codons 12 and 13 by SNaPshot Analysis in Comparison to Common DNA Sequencing

Abstract: Due to the call for fast KRAS mutation status analysis for treatment of patients with monoclonal antibodies for metastatic colorectal cancer, sensitive, economic, and easily feasible methods are required. Under this aspect, the sensitivity and specificity of the SNaPshot analysis in comparison to the commonly used DNA sequencing was checked. We examined KRAS mutations in exon 2 codons 12 and 13 with DNA sequencing and SNaPshot analysis in 100 formalin-fixed paraffin-embedded tumor tissue samples of pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…The Kras mutant-enriched polymerase chain reaction (PCR) Kits (FemtoPath®) and a following direct sequencing method were applied to analyze exon 2 of the Kras gene. The reason why we choose Kras exon 2 to analyze is because Kras gene mutations are mainly known to cluster in several hotspots, with exon 2 (codons 12 and 13) being most commonly affected [69]. …”
Section: Main Textmentioning
confidence: 99%
“…The Kras mutant-enriched polymerase chain reaction (PCR) Kits (FemtoPath®) and a following direct sequencing method were applied to analyze exon 2 of the Kras gene. The reason why we choose Kras exon 2 to analyze is because Kras gene mutations are mainly known to cluster in several hotspots, with exon 2 (codons 12 and 13) being most commonly affected [69]. …”
Section: Main Textmentioning
confidence: 99%
“…Among these genetic changes, the K-ras mutation was most frequently detected with 45%–100% frequency in the tumor tissue and a 77% frequency in the serum of patients with PC or pancreatic adenocarcinoma (PAC) [22, 43, 8788]. 50–75% patients with PAC have mutations in TP53 [43, 89].…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Secondly, we used a SNaPshot assay, which is a targeted approach that can be reliably used for small biopsies or cytology samples . There have been several reports that the SNaPshot assay is superior to conventional sequence analyses and NGS assays in both sensitivity and specificity . It is reported that tumour cell content sensitivity thresholds were 10% for a SNaPshot assay, 20% for direct sequencing and 10–0% for NGS .…”
Section: Discussionmentioning
confidence: 99%